PENGARUH KOMITMEN KARIR DAN MOTIVASI KARIR TERHADAP KESUKSESAN KARIR SUBJEKTIF KARYAWAN PADA PT BANK BTN BEKASI - Vitus Putut Surya Mahendra (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2017)
This research was conducted in order to determine whether the effect of commitmen career and career motivation towards Subjective career success of employees Bank Tabungan Negara Tbk. Sampling method used is convenience sampling. This study took a sample of 60 employees of the State Savings Bank Tbk. Methods of data analysis used in this research is multiple regression analysis. The results of data processing using SPSS 22. The research found that career commitment and career motivation have significant effect on subjective career success.